Press-konferentsiia Borisa El'tsina . Press-konferentsiia Borisa El'tsina . Press-Conference of Boris Yeltsin . Пресс-конференция Бориса Ельцина - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Discussion of the political situation in regions of the Russian Federation and other socio-political questions. Featured in the program: Yeltsin, Boris Nikolayevich (President of the Russian Federation) Обсуждение политической обстановки в регионах Российской Федерации и других социально-политических вопросов. В программе участвуют: Ельцин, Борис Николаевич (Президент Российской Федерации)